703 Engineered exosomes with altered cellular tropism achieve targeted STING agonist delivery and single-agent tumor control in vivo. (10th December 2020) - Kauke, Monique; Ross, Nikki; Burzyn, Dalia; Martin, Shelly; Xu, Ke; Lewis, Nuruddeen; Leng, Charan; Jang, Su Chul; McCoy, Christine; Yu, Stephanie; Dooley, Kevin; Sathyanarayanan, Sriram; et al.
Abstract : Background: Exosomes are natural, abundant extracellular vesicles capable of transferring complex molecules between neighboring and distant cell types. Translational research efforts have focused on co-opting this communication mechanism to deliver exogenous payloads to treat a variety of diseases. Important strategies to maximize the therapeutic potential of exosomes therefore include payload loading, functionalization of the exosome surface with pharmacologically active proteins, and delivery to target cells of interest. Methods: Through comparative proteomic analysis of purified exosomes, we identified several highly enriched and exosome-specific proteins, including a transmembrane glycoprotein (PTGFRN) belonging to the immunoglobulin superfamily. Leveraging PTGFRN as a scaffold for exosome surface display, we developed our engExTM platform to generate engineered exosomes functionalized with a variety of structurally and biologically diverse proteins.Systemically administered exosomes are primarily taken up by macrophages in the liver and spleen. To redirect exosome uptake to other cell types, we employed our engineering platform to display functional targeting ligands, including single domain antibodies, single chain variable fragments, single chain Fabs (scFabs), and receptor ligands, on the exosome surface at high density. To demonstrate that exosome surface modifications can alter cellular tropism, we generated exosomes displaying anti-Clec9A scFabs to target conventional type 1 dendritic cells (cDC1s), anti-CD3 scFabs to target T cells, and CD40 ligand to target B cells. The engineered exosomes exhibited functional antigen binding that led to greater association with the cell types expressing the cognate receptor both in vitro and in vivo. Results: In mice, systemic administration of exosomes engineered to display scFabs targeting Clec9A resulted in a 4-fold increase in the percentage of cDC1 cells in the blood that had taken up exosomes over controls, and a 6-fold increase in the number of exosomes taken up per cell. We further showed that compared to untargeted exosomes, those with altered tropism achieved increased functional payload delivery to the target cell of interest. In primary mouse dendritic cells, anti-Clec9A exosomes loaded with a cyclic dinucleotide STING agonist achieved greater pathway induction, 2.3-fold greater as measured by IFNβ production, 2-fold by IFNα, and 15-fold by IL-12, when compared to an untargeted control. Preliminary in vivo data show that intra-tumorally administered anti-Clec9A exosomes reduce the required STING agonist dose 10-fold to achieve single-agent tumor control and induce immune responses against tumor-associated antigen, compared to controls. Conclusions: These results demonstrate the potential of our engExTM platform to generate targeted exosome therapeutics capable of immune cell stimulation and tumor growth inhibition in vivo. Ethics Approval: All experimental animal studies were performed according to Codiak BioSciences IACUC approved AUP CB2020-001.